1991
DOI: 10.1177/014107689108400206
|View full text |Cite
|
Sign up to set email alerts
|

Night Sedation and Arthritic Pain

Abstract: This pilot study highlights the problems of benzodiazepine (BDP) usage in patients attending a rheumatology clinic. Of 127 consecutive patients attending the rheumatology clinic a total of 29% (37) had been taking night sedation for mean duration of 4.1 years. The majority of BDP users (92%) were women. In 78% night sedation was taken for insomnia associated with night pain. We recommend that if BDP is to be prescribed it should be only in selected cases for a short time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[10][11][12]14,15,18 Although recent national trends in benzodiazepine prescribing have not been as well documented as opioid-prescribing trends, several studies suggest increases in benzodiazepine prescribing in the U.S. 27,28 A survey of U.S. primary care visits between 2002 and 2009 found that benzodiazepine prescription rates increased 12.5% per year and rates of opioid and benzodiazepine co-prescription increased 12.0% per year. 27 This is consistent with the increases in AAPCs for overdose deaths and ED visits seen in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12]14,15,18 Although recent national trends in benzodiazepine prescribing have not been as well documented as opioid-prescribing trends, several studies suggest increases in benzodiazepine prescribing in the U.S. 27,28 A survey of U.S. primary care visits between 2002 and 2009 found that benzodiazepine prescription rates increased 12.5% per year and rates of opioid and benzodiazepine co-prescription increased 12.0% per year. 27 This is consistent with the increases in AAPCs for overdose deaths and ED visits seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that among patients who receive long-term opioids for chronic noncancer pain, 40% or more also use benzodiazepines. 10,14,15 In a study of opioidnaïve patients, benzodiazepine use was a stronger predictor of future opioid use than was musculoskeletal pain. 16 Among patients who abuse opioids, benzodiazepine abuse is prevalent also, and co-users report using benzodiazepines to enhance opioid intoxication.…”
mentioning
confidence: 99%
“…Concerning the possible nonmedical use of BZDs among patients with chronic pain, survey data has revealed that as many as 40–60% of pain patients regularly use BZDs (Hardo and Kennedy, 1991, see also Kouyanou et al, 1997). In an analysis of prescription records, Bachs et al (2008) found that those codeine users dispensed the highest amounts of the opioid, were significantly more likely to be co-using large amounts of BZDs.…”
Section: The Co-abuse Of Benzodiazepines and Opioids In Humansmentioning
confidence: 99%
“…Surveys studies have shown that as many as 40-60% of pain patients use benzodiazepines, usually on a long-term basis (Hendler et al 1980;King and Strain 1990a;Hardo and Kennedy 1991). This rate of benzodiazepine use is much greater than in the general population .…”
Section: Brain Damagementioning
confidence: 99%